2017
DOI: 10.1101/211466
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Differential and defective expression of Koala Retrovirus indicate complexity of host and virus evolution

Abstract: Koala retrovirus (KoRV) is unique amongst endogenous (inherited) retroviruses in that its incorporation to the host genome is still active, providing an opportunity to study what drives this fundamental process in vertebrate genome evolution. RNA sequencing of KoRV from koala populations with high virus burden (Queensland) and low virus burden (South Australia) identified that South Australian animals, a population previously thought to have KoRV negative animals, harboured replication defective KoRV. This dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 76 publications
(134 reference statements)
1
25
0
Order By: Relevance
“…It was thought until recently that southern animals only possessed KoRV-A 14,23 and not other variants of the virus and this might be a potential explanation for the reduced disease burden in southern animals. However our recent work has shown that South Australian animals do in fact have multiple variants of KoRV (including KoRV-B) 16,38 . The previous lack of detection of non-KoRV-A variants in southern populations is likely due to the use of relatively insensitive end point PCR for detection, together with the overall low proviral and viral loads in these populations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was thought until recently that southern animals only possessed KoRV-A 14,23 and not other variants of the virus and this might be a potential explanation for the reduced disease burden in southern animals. However our recent work has shown that South Australian animals do in fact have multiple variants of KoRV (including KoRV-B) 16,38 . The previous lack of detection of non-KoRV-A variants in southern populations is likely due to the use of relatively insensitive end point PCR for detection, together with the overall low proviral and viral loads in these populations.…”
Section: Discussionmentioning
confidence: 99%
“…These studies determined prevalence based on the presence of the KoRV proviral pol gene 14,15 . In contrast, the transcriptomic analysis of QLD and SA koalas submandibular lymph node tissue demonstrated KoRV transcripts in 100% of animals from both populations 16 , although 27.6% SA koalas were missing transcripts of pol or env or both of these genes and had only truncated transcripts of the gag gene 16 . Given these complex findings, the role of KoRV in causing differences in disease occurrence between northern and southern populations is unlikely to be due only to proviral prevalence, and other viral characteristics must be explored.…”
mentioning
confidence: 90%
“…Our understanding of the relationship between koalas and KoRV is rapidly evolving as a growing number of koalas are evaluated with increasingly sensitive methods. KoRV was originally thought to be spreading southwards after it was introduced to northern koala populations less than 200 years ago 41 , but recent analyses suggest it crossed into koalas up to 49,000 years ago 42 and a range of subtypes have been detected in both northern and southern koala populations 43 . Consistent with these analyses, we found a strikingly similar prevalence of KoRV subtypes at each of our study sites, suggesting that the spread of KoRV in this region occurred before gene flow between our populations was limited by the BVB 24 and the rapid and widespread declines in koala populations 30,000-40,000 years ago 23 .…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the presence of KoRV provirus alone is not sufficient to influence chlamydial disease progression and that subtype expression might be more important 46 . Acknowledging that KoRV detection methods have different targets and sensitivities 43,46 , further study is clearly needed to tease out the complex interactions between this putative pathogen and its host.…”
Section: Discussionmentioning
confidence: 99%
“…Yet, preservation of intact gag and env ORFs may indicate a functional importance, perhaps as restriction factors against exogenous KoRV. Moreover, some koala populations such as those located in Southern Australia (SA) are relatively resistant to KoRV induced disease and usually have low viral loads (Tarlinton et al, 2017). In contrast, koalas in northern Australia such as Queensland suffer from higher viremia and disease burden, and active KoRV infection is more prevalent.…”
Section: Endogenization In Real Time: Koala Retrovirusmentioning
confidence: 99%